DARI METODOLOGI MENUJU AKSI SOSIAL - agus sakroni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2016)
This article is aimed to explain how the methodology of the Alquran studies contributes positive impacts on social problems and becomes a theoretical framework applicable in practical conditions. During this time the Alquran is considered as a sacred text for some many Muslims. No doubt, the dynamic understanding of the Alquran tend to be textual and a priori due to the fear of mistakes in interpreting studies related to the historical and social facts. However, this short article is going to present a study of the Alquran although it is profane can positively contribute to the social problems of community. Hermeneutical methodology studies are clearly examined and likely to lead to one-dimensional translation which is not rigid and flexible based on the needs of the times. In addition, this study shows realities that some Muslim leaders were able to describe the spirit of the Alquran which is dynamic and prophetic to social problems.